2011
DOI: 10.1016/j.jcrs.2010.12.052
|View full text |Cite
|
Sign up to set email alerts
|

Wavefront-guided epithelial laser in situ keratomileusis with mitomycin-C for myopia and myopic astigmatism: Flap-on versus flap-off technique

Abstract: No author has a financial or proprietary interest in any material or method mentioned.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(23 citation statements)
references
References 19 publications
1
22
0
Order By: Relevance
“…Six RCTs and 3 comparative studies published between 2008 and 2011 met the inclusion criteria [7,8,9,13,14,15,16,17,18]. A total of 489 patients (958 eyes) underwent off-flap epi-LASIK and on-flap epi-LASIK.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Six RCTs and 3 comparative studies published between 2008 and 2011 met the inclusion criteria [7,8,9,13,14,15,16,17,18]. A total of 489 patients (958 eyes) underwent off-flap epi-LASIK and on-flap epi-LASIK.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 489 patients (958 eyes) underwent off-flap epi-LASIK and on-flap epi-LASIK. Patients’ mean age ranged from 20.25 to 33 years and the mean preoperative manifest spherical equivalent (MSE) ranged from –3.49 D to –9.14 D; 0.02% mitomycin C (MMC) was used for 15–120 s in 6 studies [9,13,14,16,17,18]. Each study revealed that there were no significant differences in preoperative demographic features and other factors that may have influenced surgery.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations